Fasilitas Eco Lodge dengan Pendekatan Tema Eko Arsitektur di Desa Jati Luwih Tabanan: Bahasa Indonesia - I Gusti Bagus Ananda Kusuma; I Nyoman Gede Maha Putra; Ni Wayan Nurwarsih (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Tourist accommodation in the Jati Luwih Tourism Village mostly still pays little attention to the surrounding natural environment which should be a potential for the village. With the existence of Eco-Lodge tourist accommodation facilities, it is hoped that it will be an example for the community or investors in planning future tourist accommodations to pay more attention to the natural environment, even better for the good of the environment of Jati Luwih Tourism Village. Eco-Lodge Accommodation is an eco-friendly lodging accommodation facility, this facility offers the beauty of the natural environment as a potential for tourists to enjoy this facility. This accommodation facility pays attention to the natural environment by minimizing damage to the existing environment and making the existing environment as potentialabove and the keywords that are formulated must be specific and answered in the sub-section of the discussion.